Maiden [videorecording (DVD)] - Holmes, Alex; Edwards, Tracy, 1962-; Edwards, Tracy, 1962- (Sony Pictures Home Entertainment, 2019)
The true story of skipper Tracy Edwards and the first all-female crew to enter the Whitbread Round the World race.